Culture of Ukrainian Scientific Language: Oral and Written Forms of Professional Communication - Kostusiak, Nataliia; Hromyk, Larysa; Hrytsevych, Yurii; Kryskiv, Myroslava; Sydorenko, Olha; Shumenko, Olha (My University, 2025)
The article comprehensively analyzes the modern Ukrainian scientific language in its oral and written forms with an emphasis on the internal organization, functional-stylistic, lexical, grammatical, communicative pragmatic features of texts of various genres, as well as in plane of academic ethics and the implementation of speech strategies and tactics, which enabled a multidimensional interpretation of the object under study. The focus is made on typical models of professional communication in the scientific field report, scientific message, dispute, monograph, article, theses, etc., their linguistic (lexical, morphological, and syntactic units), compositional and logical structure. Normative and non-normative words and their compounds, attested in scientific works of various genres and in oral monological and dialogical professional speech, are highlighted. Deviations from the stylistic norms of the Ukrainian language are identified and described, with an emphasis on stylistic figures and tropes, the sphere of expression of which is mainly oral professional speech. The specificity of lexical units that serve as a means of linguistic manipulation in disputes, as well as those that give emotionality, expressiveness, unorthodoxy to public speeches, and attract the attention of listeners, is emphasized. It is traced that the oral and written forms of scientific language, despite the presence of common features, in particular, objectivity, accuracy, argumentation, etc., have a number of different parameters. The oral form of scientific language is characterized by extensive syntactic variation, spontaneity, and the presence of some elements that give speech emotionality. In contrast, written works of various genres are characterized by a higher level of completeness, normativity, and a clear, logically and structurally motivated construction of sentences. It was found that mastery of the norms of the Ukrainian scientific language, a high level of professional communication culture, and skillful use of vocabulary serve as important factors in forming the image of a modern highly qualified researcher who is able to analyze and objectively evaluate the achievements of specialists in a certain field, effectively argue own position, and present own research results in an orderly, accurate, and understandable manner.
Keywords: Scientific style; Ukrainian scientific language; Academic rhetoric; Rhetorical skil; Academic writing; Professional communication; Intercultural communication; Language norms; Culture of the Ukrainian language